Experiential Meaning Analysis on “Try Everything” Song By Shakira - Naomi Simanjuntak; Selviana Napitupulu (PT. Intelek Cendikiawan Nusantara, 2026)
This research analyzes the experiential meaning in Shakira’s song “Try Everything” using Halliday’s (1994) transitivity framework within Systemic Functional Linguistics. Employing a descriptive qualitative design, the research examines processes, participants, and circumstances in the lyrics to reveal how human experiences of perseverance, optimism, and personal growth are constructed. Findings indicate that material processes dominate, highlighting actions, repeated efforts, and resilience in overcoming challenges. Mental processes convey desire, awareness, and acceptance of failure, representing internal reflection, while relational processes express general truths and shared human experiences. Verbal processes function as encouragement and self-affirmation, engaging listeners directly. Circumstances of time, cause, purpose, and concession provide context, situating experiences in realistic conditions. Overall, the interaction of these transitivity elements demonstrates that the song communicates motivational messages through multidimensional representations of action, cognition, relational values, and communication. This research contributes to understanding how inspirational music conveys human experience and positive life values through linguistic choices.